Is it Worth Getting a Doctorate? - Polónyi, István (Central European Journal of Educational Research, 2022)
PhD training is part of the global education competition. The number of doctoral students per 100,000 people is a feature that moves together with the scientific performance of a country. Thus, doctoral training is an important element of a country’s innovation, in which Hungary is lagging behind. We assume that the main reason for the limited amount of doctoral students in Hungary is the low level of individual demand for training which, in turn, is due to the fact that the academic career of doctoral students promises low earnings compared to the placement of university graduates in other spheres. The earnings test and life earnings analysis presented by the study support this assumption: the earnings of those entering academically qualified academic careers are significantly lower than those of graduates working in the corporate sector. Though there are limitations present which impede the generalizability of these results, it does call to attention important trends to be acknowledged in future research.